DEPLETED TO REFERTILIZED MANTLE PERIDOTITES HOSTING CHROMITITES WITHIN THE TUNCELI OPHIOLITE, EASTERN ANATOLIA (TURKEY): INSIGHTS ON THE BACK ARC ORIGIN - Çimen, Okay; Toksoy-Köksal, Fatma; Öztüfekçi-Önal, Ayten; Aktağ, Alican (Ofioliti, 2016)
The Tunceli Ophiolite, which represents the eastern part of the Izmir-Ankara-Erzincan Suture Belt (IAESB), hosts several chromite mines. The petrological characteristics of these deposits and their host rocks were investigated here for the first time. This ophiolite includes serpentinized peridotites, harzburgites, dunites, gabbros, sheeted dykes, pillow lavas and mudstones. The chromite occurrences are hosted in the mantle peridotites. The spinel group minerals in the ore and in ultramafic samples were sampled in seven different chromite mines (Yıldırım, Aksu, Hasangazi, Atilla, Eskigedik, Işıkvuran and Oymadal). The chromitite spinels display podiform characteristics. The Cr# = (0.39-0.89) and Mg# = values (0.43-0.74 ) of these spinel group minerals mainly correspond to magnesiochromite and chromite compositions. The silicate assemblage of the cpx-poor harzburgites include Mg-rich olivine (Fo91), enstatite and diopside. The occurrence of Ti-enriched secondary clinopyroxenes likely reflect refertilization processes which may have originated by interaction between Ti-rich melts and highly depleted peridotites. The average Cr2O3 (15.46 %wt) and ΣPGE (92.10 pbb) contents of the chromitites from the Tunceli ophiolite are lower than those of other chromitite-bearing ophiolites in Turkey. The consistent geochemical and mineral chemistry data from the mantle peridotites and chromitites within the Tunceli Ophiolite suggest formation in an intra-oceanic back-arc basin which may have been active during the closure of northern branch of the Neotethyan ocean.